Investigating Engineering Students’ Needs for ICT Integration in ESP Classes - Belabcir, Souad (Journey: Journal of English Language and Pedagogy, 2024)
The innovations in science and technology and the continuous development of educational theories and methods have urged the need for creative uses of Information and Communication Technology (ICT) in English language teaching in Moroccan Higher Education and especially in the teaching and learning of English for Specific Purposes (ESP). For this reason and others, the present study aims to investigate the integration of ICT in ESP classes by identifying engineering students’ needs for ICT integration in ESP classes at the Engineering school (ENSAM), Meknes. To meet this aim, the study adopted a quantitative method approach, which utilized a close-ended questionnaire administered to 64 civil engineering students. The data gathered was analyzed through Statistical Package of Social Sciences (SPSS). The results revealed the significance of ICT integration in ESP classes for Engineering students. Furthermore, the students expressed a number of lacks and necessities to improve their English proficiency level in general. The current research contributes to expanding literature on ESP in Morocco. Additionally, the implications and recommendations proposed will guide future practices and reforms in ESP teaching and learning.